Effect of remote ischemia or nicorandil on myocardial injury following percutaneous coronary intervention in patients with stable coronary artery disease: A randomized controlled trial. (1st June 2017) - Miyoshi, Toru; Ejiri, Kentaro; Kohno, Kunihisa; Nakahama, Makoto; Doi, Masayuki; Munemasa, Mitsuru; Murakami, Masaaki; Takaishi, Atsushi; Kawai, Yusuke; Sato, Tetsuya; Sato, Katsumasa; Oka, Takefumi; et al.
Abstract: Background: The effect of remote ischemic preconditioning (RIPC) and nicorandil on periprocedural myocardial injury (pMI) in patients with planned percutaneous coronary intervention (PCI) remains controversial. The aim of this randomized trial was to evaluate the effect of RIPC or nicorandil on pMI following PCI in patients with stable coronary artery disease (CAD) compared with a control group. Methods: Patients with stable CAD who planned to undergo PCI were assigned to a 1:1:1 ratio to control, RIPC, or intravenous nicorandil (6 mg/h). Automated RIPC was performed by a device, which performs intermittent arm ischemia through three cycles of 5 min of inflation and 5 min of deflation of a pressure cuff. The primary outcome was the incidence of pMI, determined by an elevation in high-sensitive troponin T or creatine kinase myocardial band at 12 or 24 h after PCI. The secondary outcomes were ischemic events during PCI and adverse clinical events at 8 months after PCI. Results: A total of 391 patients were enrolled. The incidence of pMI following PCI was not significantly different between the control group (48.9%) and RIPC group (39.5%; p  = 0.14), or between the control group and nicorandil group (40.3%; p  = 0.17). There were no significant differences in ischemic events during PCI or adverse clinical events within 8 months after PCI among the three groups. Conclusions: This study demonstrated moderate reductions in biomarker release and pMI by RIPC or intravenous nicorandil prior to the PCI consistently, but may have failed to achieve statistical significance because the study was underpowered.